Pengaruh Tingkat Suku Bunga, Reward Dan Promosi Terhadap Minat Menabung Nasabah Bank Bri Unit Yos Sudarso - Karolina A. Rewa; Martinus Ludji (Universitas Kristen Wira Wacana Sumba, 2013)
Bank as financial institutions are part of the factors driving economic activity, which has always tried to offer a variety of instruments to attract customers to save them by raising the interest rate savings, giving a gift (reward), as well as promotions to introduce the products offered to customers.PT. BRI unit Yos Sudarso Waingapu is one bank that seeks to provide quality services to customers in the city of Waingapu. The research objective was to determine the effect of interest rates, reward, and promotion of the interests of saving the customers of Bank BRI Yos Sudarso. The results showed that two independent variables, namely interest rates and promotion have a positive and significant effect on the interest of saving the customer while the independent variable is the reward does not have a significant impact on customers' interest in saving Bank BRI Yos Sudarso.Keywords: interest rates, rewards, promotions, savings interest, Customers, Banks